2021
DOI: 10.1021/jacs.1c08348
|View full text |Cite
|
Sign up to set email alerts
|

Ternary Alloys Enable Efficient Production of Methoxylated Chemicals via Selective Electrocatalytic Hydrogenation of Lignin Monomers

Abstract: We explore the selective electrocatalytic hydrogenation of lignin monomers to methoxylated chemicals, of particular interest, when powered by renewable electricity. Prior studies, while advancing the field rapidly, have so far lacked the needed selectivity: when hydrogenating lignin-derived methoxylated monomers to methoxylated cyclohexanes, the desired methoxy group (−OCH 3 ) has also been reduced. The ternary PtRhAu electrocatalysts developed herein selectively hydrogenate lignin monomers to methoxylated cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 43 publications
(62 reference statements)
1
34
0
Order By: Relevance
“…This deduction allows for the correlation of ECH kinetics with binding energies, consistent with the recent identification of lignin electrochemical reduction. 39…”
Section: Resultsmentioning
confidence: 99%
“…This deduction allows for the correlation of ECH kinetics with binding energies, consistent with the recent identification of lignin electrochemical reduction. 39…”
Section: Resultsmentioning
confidence: 99%
“…Guaiacol was selected as a suitable internal standard for this quantitative analysis. The activity of the reaction was evaluated using the following indicators: 28,31,32 Faradaic efficiency (FE) of products:…”
Section: Product Analysismentioning
confidence: 99%
“…4. Since FE and current density are the main factors determining the plant-gate levelized cost of target products, 32 we calculated the boundary conditions of profit and found that the lowest economically practicable FE for our developed reaction system is 29.5% at a current density of 50 mA cm −2 , at which the corresponding plant-gate levelized cost of COL equals its market price of 8955.20 $ per ton. Actually, this work has achieved an FE of 41.15% for COL at a current density of 50 mA cm −2 and the corresponding TEA result revealed that the plant-gate levelized cost of ECH technology for COL is about 5532.37 $ per ton, far lower than its market price.…”
Section: Preliminary Techno-economic Analysis (Tea)mentioning
confidence: 99%
“…As a result, PtRhAu electrocatalysts achieve a record 58 % faradaic efficiency toward 2-methoxycyclohexanol from the lignin monomer guaiacol at 200 mA/cm 2 . [132]…”
Section: Electrocatalysismentioning
confidence: 99%
“…It was found that Rh and Au modulate the electronic structure of Pt and this modulating steers intermediate energetics on the electrocatalyst surface to facilitate the hydrogenation of lignin monomers and suppress C‐OCH 3 bond cleavage. As a result, PtRhAu electrocatalysts achieve a record 58 % faradaic efficiency toward 2‐methoxycyclohexanol from the lignin monomer guaiacol at 200 mA/cm 2 [132] …”
Section: Chemical Catalytic Depolymerization Of Ligninmentioning
confidence: 99%